2022
DOI: 10.1002/ejp.1955
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on patients with chronic pain in Germany: Associations with expectations and control beliefs

Abstract: Background While the COVID‐19 pandemic is affecting people's well‐being worldwide, it may place a particularly high burden on people with chronic pain, as pain is known to be influenced by societal and psychological conditions. Methods In this observational study, we conducted telephone interviews with 196 patients with chronic pain to assess the impact of the pandemic on various aspects of their pain and everyday life. The initial interviews were conducted between Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…In line with previous reports by Müßgens et al [4], we observed that approximately half of those suffering from chronic pain experienced either symptom aggravation or no improvement in their pain during the COVID-19 pandemic. An improvement in symptoms during this period was rather the exception.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with previous reports by Müßgens et al [4], we observed that approximately half of those suffering from chronic pain experienced either symptom aggravation or no improvement in their pain during the COVID-19 pandemic. An improvement in symptoms during this period was rather the exception.…”
Section: Discussionsupporting
confidence: 93%
“…In total, 3 Mean. 4 Standard deviation. 5 For the sake of simplicity, the two VR-12 subgroups, MCS and PCS, have been summarized in a VR-12 total mean score.…”
Section: Sociodemographic Medical and Psychometric Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In those with chronic pain, the evidence suggests similar disruptions with decreased access to care, 11,12 adverse impacts to both physical and mental health, 13 and increased pain‐related interference and pain anxiety 14–17 . Wait times for appointments and procedures were increased, in some cases indefinitely 18 .…”
Section: Introductionmentioning
confidence: 99%
“…and increased pain-related interference and pain anxiety. [14][15][16][17] Wait times for appointments and procedures were increased, in some cases indefinitely. 18 Finally, for some with chronic pain, the pandemic and its consequent changes to healthcare resulted in challenges to prescription access.…”
mentioning
confidence: 99%